2019
DOI: 10.21203/rs.2.12997/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Age-dependent impact of breast cancer risk perception on mammography screening behavior in Brazilian women

Abstract: Background: Previous studies suggest that education and income affect Brazilian women’s breast cancer prevention behavior. The present study focused on the impact of perceived risk on mammography screening behavior. Methods: Information regarding socioeconomic variables and risk perception was obtained from 396 healthy women aged 40 - 79 years. Absolute and comparative perceived risk was measured on a seven-point Likert scale. Perceived numeric risk was measured on a percentage scale A Breast Cancer Risk Asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
(35 reference statements)
1
0
0
Order By: Relevance
“…The present data indicated that a family history of breast cancer is associated with individual and comparative risk perception. This is consistent with previous research [46], in which family history shows an increased risk perception. However, the Emirati students with a family history of BC showed a lower perceived individual and compared risk than the Portuguese.…”
Section: Discussionsupporting
confidence: 94%
“…The present data indicated that a family history of breast cancer is associated with individual and comparative risk perception. This is consistent with previous research [46], in which family history shows an increased risk perception. However, the Emirati students with a family history of BC showed a lower perceived individual and compared risk than the Portuguese.…”
Section: Discussionsupporting
confidence: 94%